Evolution of the hypoxic compartment on sequential oxygen partial pressure maps during radiochemotherapy in advanced head and neck cancer. (January 2021) - Lazzeroni, Marta; Ureba, Ana; Wiedenmann, Nicole; Nicolay, Nils H.; Mix, Michael; Thomann, Benedikt; Baltas, Dimos; Toma-Dasu, Iuliana; Grosu, Anca L.
Highlights: Repeated PET imaging of hypoxia may be pivotal in radiotherapy outcome prediction. Oxygen partial pressure maps can be non-linearly derived from radiotracer uptake. The hypoxic target volume evolution in extension and severity can be determined. The first two treatment week parameters have potential for outcome prediction. Information may be used for treatment adaptation personalised strategies. Abstract: Background and purpose: Longitudinal Positron Emission Tomography (PET) with hypoxia-specific radiotracers allows monitoring the time evolution of regions of increased radioresistance and may become fundamental in determining the radiochemotherapy outcome in Head-and-Neck Squamous Cell Carcinoma (HNSCC). The aim of this study was to investigate the evolution of the hypoxic target volume on oxygen partial pressure maps (pO2 -HTV) derived from 18 FMISO-PET images acquired before and during radiochemotherapy and to uncover correlations between extent and severity of hypoxia and treatment outcome. Material and methods: 18 FMISO-PET/CT images were acquired at three time points (before treatment start, in weeks two and five) for twenty-eight HNSCC patients treated with radiochemotherapy. The images were converted into pO2 maps and corresponding pO2 -HTVs (pO2 -HTV1, pO2 -HTV2, pO2 -HTV3 ) were contoured at 10 mmHg. Different parameters describing the pO2 -HTV time evolution were considered, such as the percent and absolute difference between the pO2 -HTVs (%HTVi, j and HTVi -HTVj with i, j = 1, 2, 3, respectively) and the slope of the linear regression curve fitting the pO2 -HTVs in time. Correlations were sought between the pO2 -HTV evolution parameters and loco-regional recurrence (LRR) using the Receiver Operating Characteristic method. Results: The Area Under the Curve values for %HTV1, 2, HTV1 -HTV2, HTV1 -HTV3 and the slope of the pO2 -HTV linear regression curve were 0.75 (p = 0.04), 0.73 (p = 0.02), 0.73 (p = 0.02) and 0.75 (p = 0.007), respectively. Other parameter combinations were not statistically significant. Conclusions: The pO2 -HTV evolution during radiochemotherapy showed predictive value for LRR. The changes in the tumour hypoxia during the first two treatment weeks may be used for adaptive personalized treatment approaches.